Improvement of Prolactin Hormone Levels on Postpartum Mothers Taken by The Oketani Massage and Pressure in GB-21 Point - Machmudah, Machmudah; Khayati, Nikmatul; Widodo, Sri; Hapsari, Elsi Dwi; Haryanti, Fitri (Universitas Muhammadiyah Yogyakarta, 2020)
Background: Breastfeeding will provide a wide range of benefits for both mother and baby. Breastfeeding is one of the physical adaptations and processes of changing maternal roles in postpartum mothers. Not all mothers can go through this process correctly. A small amount of milk production on the first day of postpartum is one of the complaints that is often felt by mothers. The hormone prolactin is one of the factors that influence milk production. One way to stimulate the production of the hormone prolactin is by breast treatment. Breast care will affect hypopise to release the hormone progesterone, estrogen, prolactin, and oxytocin more. Objective: The purpose of this study was to identify the effect of pressure on the Jianjing GB-21 acupressure point and Oketani massage on the level of the hormone prolactin.Method: The type of this research is a quasi-experiment with the design used is a pre-post-test design with the control group. Prolactin hormone levels were examined before the intervention (on the first day) and on a ninth day. The examination was carried out using the ELISA (Enzym Linked Immunosorbent Assay) technique. Data obtained was analyzed using an independent sample T-test.Result: The study showed that there was an increase in mean values of maternal prolactin levels after oketani massage intervention and pressure on GB-21 acupressure points. The administration of a combination of interventions, namely Oketani massage and pressure at the GB-21 point, can increase the highest levels of the hormone prolactin, which is 3.41. Whereas in the control group that did not get any intervention, had the lowest levels of the hormone prolactin that is equal to 2,925Conclusion: it can be concluded that oketani massage and applying pressure at the GB-21 point can increase the levels of the hormone prolactin, respectively.